Optimisation of tapioca peel powder as natural coagulant in removing chemical oxygen demand, ammonia nitrogen, turbidity, colour, and suspended solids from leachate sample - ., Mohd-Salleh, S. N. A.; ., Shaylinda M. Z. N.; Othman, N.; Yashni, G. (Penerbit UTHM, 2020)
Development of natural coagulant is trending these days, especially among the researchers and the practitioners in the water and wastewater treatment industry. In this study, a natural coagulant made from agro-waste of tapioca peel was developed, and its performance had been tested by applying it on the highly polluted wastewater; leachate. The tapioca peel powder (TPP) was extracted from the white flesh of the peel itself. After several processes, the next step was to sundry the solution, and grind the dried tapioca peel until it became a fine powder. A series of jar test was carried out to study the optimisation processes by considering the concentration of the solution, the coagulant dosage, and the pH of the wastewater. Based on the optimisation process, it was determined that TPP worked optimally at 1% concentration, 1,000 mg/L of dosage, and at pH 3 of leachate by removing out 40.3% of chemical oxygen demand (COD), 18.2% of ammonia nitrogen, 85.7% of turbidity, 80.2% of colour, and 85.5% of suspended solids. Hence, it was denoted that TPP could perform satisfactorily at the right conditions with respective optimisation processes.